Firm Age and Wages - Brown, Charles; Medoff, James L. (Journal of Labor Economics, 2003)
We analyze the relationship between how long an employer has been in business (firm age) and wages. Using data from special supplements to the Survey Research Center’s monthly Survey of Consumers, we find that firms that have been in business longer pay higher wages (as previous studies found), but when we control for worker characteristics, the relationship becomes insignificant or negative. There is some evidence that the relationship is not monotonic, with wages falling and then rising with years in business. Established employers appear to make greater use of back‐loaded compensation, consistent with their higher probability of remaining in business.